Relationship Between Social Identity of Football Supporters and Conflicts (Study of The Jakmania Depok City) - Kaligis, Retor AW (Komunitas, 2020)
This study examined the relationship of The Jakmania's social identity with the conflict of supporters. The Jakmania members who come from various ethnic and regions sought identity as "Jakarta youth" which means "Metropolitan youth". This study used a convergent parallel mixed method. The survey population was members of The Jakmania Depok City who, although not living in Jakarta, supported Persija as a Jakarta football club. Semi-structured interviews were carried out to key informants involved in forming The Jakmania's social identity since the organization was founded and organizational decision makers. After being analyzed separately, the results are compared to see how far quantitative and qualitative findings confirm each other. The results of this study indicated that the members of The Jakmania, whose background is in the socio-economic status of the lower middle class, have a mixture of group pride and cathartic pressure on life. The effort to build the social identity of The Jakmania supporters gave birth to positive energy in the form of solidarity and member participation without being based on ethnicity. Likewise, the respondents from The Jakmania Depok who have Betawi parents, their identification with The Jakmania as an in-group is cross-ethnicity and regional. On the other hand, negative energy creates a supporter conflict from some members and at the same time raises corrections from within the organization to improve it.